Epidemiology of potential drug- drug interactions in hospitalized patients with type 2 diabetes mellitus in China: a retrospective study - Ren, Weifang; Liu, Yujuan; Jiang, Huaqiao; Lv, Xiaoqun; Zhang, Ning (Frontiers in Endocrinology, 2024)
Background: Combination therapy was associated with an increased risk of drugdrug interactions (DDIs) in patients with type 2 diabetes mellitus (T2DM). The present study aimed to investigate the epidemiology of potential DDIs (pDDIs), 2 including potential chemical drug-drug interactions (pCDIs) and potential herb-drug interactions (pHDIs), and classify the influencing factors of pDDIs in these patients.Methods: A retrospective study of the epidemiology of pDDIs among T2DM hospitalized patients older than 18 years and treated with at least two drugs during hospitalization was conducted over a 12-month period in 2019. PDDIs were identified with C (monitor therapy), D (consider therapy modification), and X (avoid combination) risk ratings. Binary logistic regression was used to analyze the risk factors of pDDIs. Results: A total of 6796 pDDIs were identified from 737 T2DM hospitalized patients during hospitalization, with 0.87% classified as X risk rating, 13.39% as D risk rating. Additionally, 1753 pDDIs were identified after discharge, with 0.11% as X and 25.73% as D risk rating. The drug-drug association networks showed that the majority of pCDIs were associated with cardiovascular system drugs.. Chlorphenamine-potassium chloride and danshen-warfarin were the most prevalent interacting pairs of pCDIs and pHDIs with X rating during hospitalization.Multivariate analysis indicated that the likelihood of developing over 4 pDDIs was significantly higher among T2DM patients who had received over 8 medications. The presence of pDDIs after discharge was strongly associated with the complications of T2DM and the number of discharge medications. Conclusions: T2DM patients were frequently exposed to pDDIs, including pCDIs and pHDIs, both during hospitalization and after discharge. Multi-drug combination was the primary risk factor for pDDIs.Strategies such as enhancing the monitoring and warning for pDDIs, increasing clinical pharmacological experience, as well as developing universally applicable 3 clinical guidelines for pDDIs may be beneficial in reducing the incidence of potentially harmful drug-combinations.